2020
DOI: 10.1021/acs.jpcb.0c07147
|View full text |Cite
|
Sign up to set email alerts
|

Viscosity and Structure of Water and Ethanol within GO Nanochannels: A Molecular Simulation Study

Abstract: The behavior of liquids in two-dimensional (2-D) graphene oxide (GO) nanopores is important for developing GObased nanoscience and nanofluidics. Herein, molecular dynamics simulation was carried out to study the equilibrium structures and shear viscosity for water and ethanol confined within 2-D GO nanochannels. It was observed that both species obviously exhibit structured features near GO surfaces. The confined viscosities are anisotropic with axial shear viscosity larger than vertical viscosity. The axial s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 66 publications
2
11
0
Order By: Relevance
“…It has been reported that the self-diffusion coefficient of ethanol in bulk mixture decreases with an increase in ethanol concentration and passes through a minimum around x EtOH = 0.2–0.25 in the blends. However, results show that the diffusion coefficient of confined ethanol and water molecules reduces with increasing the mole fraction of ethanol (i.e., up to x EtOH = 0.5) in the mixtures, which is akin to the behavior found in previous MD studies of confined ethanol–water in the hydrophilic or hydrophobic surfaces. ,, This might be because water and ethanol molecules strongly adsorb near the hydrophilic mica and hydrophobic graphene sheets, respectively. The diffusivities of ethanol in nanopores at different concentrations and temperatures vary from 10 –11 to 10 –9 which is in line with the previously reported simulation value of the diffusion coefficient of ethanol confined in different nanopores. ,, However, the lateral diffusion coefficient of confined ethanol in the experiment , ranges from 10 –15 to 10 –14 , which is approximately 4–5 orders of magnitude lower than the simulation value. This difference in the diffusion coefficient of ethanol is due to ethanol molecules forming 2D islands in between an ice-like water layer and flexible hydrophobic graphene.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…It has been reported that the self-diffusion coefficient of ethanol in bulk mixture decreases with an increase in ethanol concentration and passes through a minimum around x EtOH = 0.2–0.25 in the blends. However, results show that the diffusion coefficient of confined ethanol and water molecules reduces with increasing the mole fraction of ethanol (i.e., up to x EtOH = 0.5) in the mixtures, which is akin to the behavior found in previous MD studies of confined ethanol–water in the hydrophilic or hydrophobic surfaces. ,, This might be because water and ethanol molecules strongly adsorb near the hydrophilic mica and hydrophobic graphene sheets, respectively. The diffusivities of ethanol in nanopores at different concentrations and temperatures vary from 10 –11 to 10 –9 which is in line with the previously reported simulation value of the diffusion coefficient of ethanol confined in different nanopores. ,, However, the lateral diffusion coefficient of confined ethanol in the experiment , ranges from 10 –15 to 10 –14 , which is approximately 4–5 orders of magnitude lower than the simulation value. This difference in the diffusion coefficient of ethanol is due to ethanol molecules forming 2D islands in between an ice-like water layer and flexible hydrophobic graphene.…”
Section: Resultssupporting
confidence: 90%
“…The selectivity of ethanol molecules is greater in the hexagonal boron nitride slit nanopore than graphene pore . A recent study shows a higher shear viscosity of the ethanol–water mixture confined in graphene oxide (GO) nanopores in an axial direction compared to the perpendicular direction of pore walls . It has been found that confinement significantly affects the viscosity of ethanol molecules compared to water molecules, and the viscosity decrease with the nanopore width …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, larger interlayer distance can lead to a larger distance between two secondary ones. Similar multilayer phenomena have been observed for water molecules within other 2-D confinements. ,, , As water molecules enter into subregion 2 from −40 to −35 Å, most of their structural distributions are identical to those in subregion 2 except for the HCG6 system by comparing Figure b with Figure a. In the HCG6 system, two secondary ones show a certain integration toward each CNT orifice although the subregion is still far away from the CNT orifice.…”
Section: Resultssupporting
confidence: 70%